PENGARUH PERBANDINGAN TEPUNG KACANG HIJAU (Vigna radiata) DAN TERIGU TERHADAP KARAKTERISTIK BAKSO ANALOG - ., Utafiyani; Ari Yusasrini, Ni Luh; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This aims of this research was to know the effect of comparison between green bean flour and wheat flour on characteristic of analogue meatball and to know the right comparison of green bean flour and wheat flour to produce analogue meatball with the best characteristics. The design used in this research was completely randomized design (CRD) with the comparison between green bean flour and wheat flour i.e. (70 g :30 g), (60 g :40 g), (50 g :50 g), (40 g :60 g), and (30 g :70 g). Data were analysed by analysis of variance, followed by Duncan test. The result of this research showed that the comparison between green bean flours and wheat flour had no real effect on water content and aroma of analogue meatball, but significant effects were found on ash content, protein content, fat content, crude fiber content, texture, sensory characteristic such as color, flavour, texture, and overall acceptance of analogue meatball. The best characteristic of analogue meatball was comparison between green bean flour and wheat flour 30 g : 70 g i.e. 59.00 percent of water content, 1.34 percent of ash content, 6.88 percent of protein content, 1.77 percent of fat content, 1.77 percent of crude fiber content, level of elasticity 6.38 N, color (liked), aroma (neutral), texture (liked) with chewy characteristics, with the taste is rather not typical of green beans and liked, and overall acceptance (liked).